Comportamento informacional e mineração textual no Twitter - Pinto, Guilherme Franco Silva (2018)
This work aims to explore the information behavior of social media users, on Twitter specifically, at the moment they are searching and sharing information on Copyright Laws and its related subjects. Taking in consideration the social, cultural and economic changes that social media has made possible, this project will explore how the adapted Copyright Laws to digital platforms affect the usability of these platforms, and how its users seek information related to those adaptations. The Twitter API was used to collect the posts (tweets) made on the platform that are about Copyright and its related subjects, such as open licenses, Creative Commons, public domain, etc. Then, using Text Mining analysis in the statistical computing environment R, it was possible to assess and relate the terms and words used on these posts with the most common doubts and questions regarding Copyright. Finally, in this data it was possible to identify instances of information behavior of Twitter users during their interactions with each other and the information available on Twitter.